Productivity of Online learning Media For Student Disabilities In Biology Class during Social Distancing Pandemic - Risnita Risnita; Dian Cita Sari (International Journal of Disabilities and Social Inclusion, 2021)
The duration of biology class for student disabilities at the Madrasah Aliyah level has decreased since the implementation of social distancing pandemic and online learning was implemented. This presents a challenge to improve learning by developing media so that madrasah students with disabilities have more time to study independently during the lockdown period. Therefore, the researcher wanted to compare the productivity of various learning media such as text, video and video-text combination. This research was conducted using a quasi-experimental post-test method by comparing the retention of madrasah students with disabilities before the science practicum between the intervention groups. This experimental research was conducted on madrasah students with disabilities who were randomly divided into 3 groups, text (guidebook), audiovisual and text-video combination. The videos and texts were prepared by the Biology subject teacher. The results showed that the mean score was 35.1 (text group), 58.1 (video group) and 85.2 (text-video combination group). Statistical analysis using Mann Whitney showed that there were significant differences in knowledge retention between the text and video groups and between the video and text-video combination groups. The conclusion of this study is the use of multimedia can increase knowledge retention in subject matter.